2006
DOI: 10.1191/0269215506cr948oa
|View full text |Cite
|
Sign up to set email alerts
|

Statistical methods for analysing Barthel scores in trials of poststroke interventions: a review and computer simulations

Abstract: To facilitate comparison and meta-analysis, we recommend that mean values (with standard deviations or standard errors) of Barthel scores should be routinely reported in trials of poststroke interventions. The rank sum test appears the most powerful inferential technique for detecting differences in Barthel scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Outcome scale cutoff values were determined based on those in earlier literature. 17,22 Results for this study are reported as statistically significant if the p value was less than 0.05.…”
Section: Methodsmentioning
confidence: 94%
“…Outcome scale cutoff values were determined based on those in earlier literature. 17,22 Results for this study are reported as statistically significant if the p value was less than 0.05.…”
Section: Methodsmentioning
confidence: 94%
“…Previous research has demonstrated the reliability of phone BI assessments [ 17 ]. The scale may be analyzed as a continuous variable for increased power to detect associations, ability to describe the course of change over time in linear form, and avoidance of potential misclassification due to crude categorization [ 18 20 ]. BI measurements from the time of MRI forward were included.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has demonstrated the reliability of phone assessments of function using the BI (Shinar et al, 1987 ). Although it is an ordinal scale, the scale may be analyzed as a continuous variable for increased power to detect associations, ability to describe the course of change over time in linear form, and avoidance of potential misclassification due to crude categorization (Song et al, 2006 ; Bath et al, 2007 ; Saver, 2011 ).…”
Section: Methodsmentioning
confidence: 99%